Paduan Massage Effleurage dan Zingiber Officinale Oil Dalam Menurunkan Intensitas Dismenore Primer Pada Remaja: Paduan Massage Effleurage dan Zingiber Officinale Oil Dalam Menurunkan Intensitas Dismenore Primer Pada Remaja - Nyna PuspitaNingrum; Solichatin (PROFESSIONAL HEALTH JOURNAL, 2023)
Menstruation and breast enlargement in female adolescents are physical characteristics that these adolescents are entering puberty. The menstrual period begins when the reproductive organs are mature or capable of producing eggs. Menstruation is a physiological thing that occurs in female adolescents. Although physiologically, menstrual complaints are considered as disturbing things such as pain, nausea, joint pain or often called dysmenorrhea. Efforts were made to take medicine and sleep, but some claimed to have allergic reactions such as swollen eyes and even shortness of breath. Treatment with natural methods or ingredients is currently believed to be used to overcome dysmenorrhea complaints. The methods are effleurage massages that scientifically proven to reduce menstrual pain and the ingredients used are Ginger (Zingiber officinale oil) which contains shogaol and gingerol compounds that can effectively reduce menstrual pain. Objectives: This study aims to examine the effects of combinations treatments between massages and herbal medicine which can overcome complaints of dysmenorrhea. Methods: This study used a pre-experimental design with a one group pretest posttest design. The population was female students at SMK 2 Malang who were selected by purposive sampling to obtain a sample size of 74 respondents. Then the data were tested for homogeneity and analyzed by paired t test. Results: Based on the data collected from the research respondents, it is known that the results of the Fisher homogeneity test have a P value (0.522), which means that the data is homogeneous. The results of the paired T test show that T count (21.182) which is greater than T table (1.993). Conclusions: Based on the test results, there was a decrease in the pain experienced by the respondents, this proves that the application of zingiber oil can prevent or reduce the rate of dysmenorrhea in respondents.